2018
DOI: 10.15580/gjas.2018.9.091018133
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Fadama III Development Project on Beneficiaries in Nasarawa State, Nigeria

Abstract: This research was carried out to assess the impact of Fadama III project on beneficiaries in Nasarawa State, Nigeria. Two hundred and twenty respondents, who were beneficiaries were selected for the study using Multi-stage, stratified and simple random sampling techniques. Primary data were collected using a structured questionnaire. Research findings revealed that most of the respondents were aged between 31 and 35 years (28.6%), predominantly male (63.2%), had a household size of 4-6 persons (40.9%), possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This finding implies that the beneficiaries had an increases of N55,031.61 (194%) in their mean per capita income after benefiting from Fadama I project support. This finding is in line with [13] who assess the impact of Fadama III on beneficiaries by comparing their income and yield before, and after they became beneficiaries, their research findings revealed that there was a mean difference of N 224, 386.1 in the income of beneficiaries after becoming members of Fadama III project.…”
Section: Impact Of the Project Intervention On Beneficiaries' Incomesupporting
confidence: 83%
“…This finding implies that the beneficiaries had an increases of N55,031.61 (194%) in their mean per capita income after benefiting from Fadama I project support. This finding is in line with [13] who assess the impact of Fadama III on beneficiaries by comparing their income and yield before, and after they became beneficiaries, their research findings revealed that there was a mean difference of N 224, 386.1 in the income of beneficiaries after becoming members of Fadama III project.…”
Section: Impact Of the Project Intervention On Beneficiaries' Incomesupporting
confidence: 83%
“…Further study on Fadama III investigated FUGs mid-term performance of the programe in Southeast Nigeria was carried out by Ugwumba & Okechukwu (2014). The work was a post assessment which did a comparative analysis on income level of beneficiaries before and after participating in Fadama project.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The paper suggested to government assistance on those inputs that generate more income to farmers. In Nasarawa state, a study conducted by Kuza, Okwoche & Age, (2018) adopting descriptive statistics, mean and student t-test, found that more of the beneficiaries were male folks with not less than six households. More beneficiaries had farming experience less than ten years.…”
Section: Empirical Reviewmentioning
confidence: 99%